Pengembangan media peta harta karun untuk pembelajaran membaca pemulaan pada siswa kelas 1 SD Negeri Serut Baru Gunungkidul - Atikah Trisna Sari; Biya Ebi Praheto (Universitas Sarjanawiyata Tamansiswa, 2023)
There is no use of media in the early reading learning of grade 1 students of SD Negeri Serut Baru, even though media is one of the external factors that can improve early reading skills. This study aims to describe the development of Peta Harta Karun media for early reading learning, describe the feasibility of Peta Harta Karun media for early reading learning, and describe students' responses to using Peta Harta Karun media for early reading learning. The type of research used is Research and Development (R&D) with Analysis, Design, Development, Implementation, and Evaluation steps. The data are collected through interviews, observations, and questionnaires, using qualitative and quantitative data analysis techniques. The result of this study is a Peta Harta Karun media for early reading learning in grade 1 elementary school students. Peta Harta Karun media is very feasible for early reading learning with a percentage of media validation of 98.75%, material validation of 97.25%, and teacher response of 100%. Students have responded positively to the Peta Harta Karun media. The students are interested and enthusiastic about Peta Harta Karun's media, so they are motivated to read well and correctly.